Evaluation of the Electronic Transmission of Medical Findings from Hospitals to Practitioners by Triangulation - Machan, C.; Ammenwerth, E.; Schabetsberger, T. (Methods of Information in Medicine, 2006)
Objectives: The need for regional, cross-institutional electronic networks in health care is steadily growing to support seamless, cooperative health care. The aim of this study is to evaluate the impact of electronic transmission between hospitals and practitioners in a Tyrolean health care network, and to derive technical and organizational points for improvement.Methods: Between March and August 2004 we carried out a triangulation-based cross-sectional study, combining a qualitative study based on semi-structured, problem-centric interviews with selected practitioners, with a quantitative study based on a standardized questionnaire survey of all the Tyrolean practitioners that receive electronic messages. The survey was designed to confirm the hypotheses which have been systematically derived from the interviews.Results and Conclusions: The results show high satisfaction and positive impact of electronic communication. The triangulation of quantitative and qualitative methods was found to be useful in order to make the definition and confirmation of the hypotheses more transparent.
Keywords: Health informatics; evaluation studies; hospital information systems; triangulation; electronic transmission of findings; regional networks